FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN EVALUASI PROGRAM DETEKSI DINI TUMBUH KEMBANG BALITA DI TAMAN POSYANDU PUSKESMAS LAMONGAN - Dita Roykhana Nabella Nur; Besar Tirto Husodo; Priyadi Nugraha Prabamurti (Jurnal Kesehatan Masyarakat (Undip), 2018)
Early detection program for infant growth in Taman Posyandu is monitoring the growth of children under five years using KMS and monitoring the development of children under five years using the development stage of children under five and pre school children. If the child is never given stimulation then the brain tissue will shrink so that the brain function will decrease. This can reduce the quality of human resources in the future. The purpose of research to analyze the factors associated with the evaluation of early detection programs to grow babies under five in Taman Posyandu Puskesmas Lamongan. The population in this study is Posyandu cadres in the work area of Puskesmas Lamongan totaling 98 people. This study uses univariate and bivariate data analysis. Data analysis technique used is Chi Square test (significance level = 0,05).The results showed that the program of detection of infant growth in Taman Posyandu Puskesmas Lamongan run well (58,2%). Most of the respondents are in age category 48-65 years old (55,1%), high education (67,3%), unemployment (59,2%), training (77,6%). Chi Square test shows that age (p = 0,026), training (p = 0,000), cadre incentive fund (p = 0,000), Posyandu infrastructure facilities (p = 0,000), guidance on the implementation of Posyandu activities (p = 0,000) early childhood early detection program. Implementation of an early infant early detection program (0,015) is related to the output of early detection program of toddler growth. Suggestions for this research is the need for training for the cadres to improve the ability of cadres in early detection of toddlers growth.